METHODS OF SELF-DEVELOPMENT FOR STUDENTS THROUGH STEAM EDUCATION - Madina Khalimova Abdisalim qizi (The Conference Hub, 2025)
This article discusses teaching methods based on the STEAM approach, as well as the development of skills in students for conducting experiments, building models, solving problems, collaborating, and working through creative processes. Additionally, it highlights the importance of providing school students not only with some ideas but also with the opportunity to apply and implement them in practice.
Keywords: STEAM, unconventional thinking, creativity, model, invention, approach, robotics, collaboration, team, adaptability.